(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article explores the concept of word combinations in language, focusing on their various types and their role in enhancing communication. It provides an in-depth look at collocations, phrasal verbs, idiomatic expressions, fixed expressions, compounds, and prepositional phrases, explaining their structures, meanings, and usage. The article emphasizes the importance of understanding these combinations for fluency and naturalness in language, highlighting how they contribute to more precise and culturally aware communication. By mastering word combinations, learners can improve both their vocabulary and grammatical skills, enabling them to communicate more effectively and with greater nuance